Analysis of Studies on Legal Protection for Persons with Disabilities Through the Principle of Equality Before the Law Towards Equality in Legal Affairs: A Meta-Analysis - Nugroho, Anastasya Adityawati; Raihanah Iffat Mahdiyah (Open Access Indonesia Journal of Social Sciences, 2024)
The principle of equality before the law is a crucial basis for protecting human rights, including for people with disabilities. However, its implementation still faces challenges in realizing substantive equality in the eyes of the law. This research aims to analyze studies of legal protection for people with disabilities through principles equality before the law with a thematic qualitative meta-analysis approach to identify dominant themes, trends and research gaps. This research uses a meta-analysis method by collecting data from 20 relevant simulation studies from 2018 to 2024. These studies were selected based on predetermined inclusion and exclusion criteria. Data were analyzed qualitatively thematically to identify dominant themes, patterns and relationships between themes. Thematic analysis yielded three main themes: (1) Accommodation and accessibility, (2) Access to justice, and (3) Awareness and participation. The Accommodation and Accessibility theme is the most dominant theme, showing the importance of ensuring the physical environment, information and technology are accessible to people with disabilities. The access to justice theme highlights the need for a justice system that is inclusive and fair for people with disabilities. Meanwhile, the awareness and participation theme emphasizes the importance of increasing public awareness and participation of people with disabilities in the decision-making process. This research concludes that legal protection for people with disabilities is through principles equality before the law still requires continued efforts. Further research is needed to explore underrepresented themes, such as health rights, property rights, and protection in emergency situations. In addition, research also needs to evaluate the effectiveness of the interventions and policies proposed in these studies.